TEKANAN PSIKOLOGIS DAN KUALITAS TIDUR PADA MAHASISWA KEPERAWATAN DI MASA PANDEMI COVID-19 - Nurhayati, Nurhayati (Jurnal Skala Kesehatan, 2022)
Abstract: Corona Virus Disease (COVID-19) is a disease that attacks the respiratory tract. This disease increases the high mortality rate, especially in Indonesia. The Indonesian government limits activities outside the home, including the teaching and learning process for teenagers. This condition causes psychological pressure and sleep quality disturbances in adolescents to increase. This research is an observational descriptive study with total sampling. Data were collected using The Depression Anxiety Stress Scale-21 (DASS-21) and the Insomnia Severity Index (ISI in the form of google form. The results of the DASS 21 measurement and the ISI measurement on nursing students stated that students who experienced depression were 32% and anxiety 28.6%, and insomnia as much as 55.8%, these results indicate that the covid 19 pandemic causes an increase in psychological stress and the incidence of insomnia in adolescents, especially nursing students. Keyword : Corona Virus (COVID-19), Psychological distress, Insomnia